Institutional Framework and Varieties of Capitalism: An Analysis of the effects of the National Business System in the Implementation of Anti-Corruption Policies in Chilean Companies - Celedon, Daniela (2016)
Corruption is a serious concern today in Chile after the scandals happened the last years related with bribery and collusion. This study makes a historical analysis of the effects of the National Business System of Chile in the implementation of anti-corruption policies and procedures to prevent corruption in Chilean companies. Using on one hand, the Institutional Theory and the Varieties of Capitalism as a conceptual foundation, the paper analyses how the economic historical development has developed the actual Chilean institutional and business culture, whereby the paper wants to demonstrate that it has led to have the major corruption scandals of the last years. On the other hand, based in the Corporate Disclosure on Combating Bribery recommended by Dissanake et. al (2011) it is analysed the actual mechanism used for Chilean Companies against corruption, using the disclose reports and policies of fifteen Plc Companies. Finally, the research concludes by recommending how Corporate Social Responsibility (CSR) can help in the implementation and commitment anti-corruption initiatives.